Liability for Administrative Offences: Standards of European Court of Human Rights and the Current State of the Legislation on Administrative Offences in Russia - SHISHKINA, Olga E.; HABIBULINA, Olga V.; REKHOVSKIY, Aleksandr F. (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018DO - 10.14505//jarle.v9.1(31).36, 2018)
Recently, there has been a substantial increase in the number of judgments delivered by the European Court of Human Rights with regard to the Russian Federation on the complaints filed by Russian citizens, including the complaints related to the liability for administrative offences. The characteristic tendency of the European Court of Human Rights to qualify administrative offences as criminal acts not only brings into focus the issue of ensuring procedural safeguards for individuals charged with administrative offences but also touches upon material aspects of the relation between criminal and administrative law-breaking in Russia as well as changes the traditional juristic view upon the essence of the legislation on administrative offence. Political and economic reforms of Perestroika and the first post-Soviet decade had a significant influence on the institution of administrative justice. Hence, on the one hand, its current state is caused by objective reasons. On the other hand, the legislator, having quite a broad discretion in determining whether to impose administrative or criminal sanctions in each particular case, has seriously blurred the material boundary between criminal and administrative offences. The problem of present-day legislation on administrative offences in Russia is a material hypertrophy of administrative liability together with continuous reduction of procedural safeguards and guarantees for individuals charged with administrative offences. The procedural norms of the existing Code of Administrative Offences of the Russian Federation cannot provide for the adversarial nature of the administrative trial due to the fact that the Code of Administrative Offences of the Russian Federation is not methodologically aimed at regulating administrative (judicial) proceedings.